Dramaturgy of Green Branding in the Algorithmic Era: A Multimodal Analysis of Ecological Persona and the Politics of Representation - Lasmita Nurana (Dinasti Publisher, 2025)
Green branding involving public figures is increasingly shaped by digital dramaturgy and multimodal strategies that construct ecological personas. In algorithm-driven environments where emotion plays a central role, environmental messaging goes beyond information delivery; it also constructs the ethical image of celebrities and the institutions they endorse of celebrities and the institutions they endorse. This research examines two visual texts Semesta, a documentary, and Jejak BuktiBaktiBCA, a corporate video to investigate how language, imagery, and gesture are orchestrated to establish ecological authenticity. The analysis reveals that public figures tactically manage their visibility, weaving together reflective narratives and emotionally resonant personal stories. These performative strategies highlight how digital dramaturgy, algorithmic patterns, and the attention economy converge. The study contributes to the fields of environmental communication by applying dramaturgical and multimodal frameworks, offering a critical perspective on affect and representation in Indonesia’s digital green branding landscape.